A rapid crosslinking injectable hydrogel for stem cell delivery, from multifunctional hyperbranched polymers via RAFT homopolymerization of PEGDA1. Issue 34 (14th September 2015) - Dong, Yixiao; Qin, Yue; Dubaa, Marie; Killion, John; Gao, Yongsheng; Zhao, Tianyu; Zhou, Dezhong; Duscher, Dominik; Geever, Luke; Gurtner, Geoffrey C.; Wang, Wenxin
<x xml:space="preserve">Abstract</x> A novel injectable hydrogel for stem cell delivery was prepared from multifunctional hyperbranched polyPEGDA and thiolated hyaluronic acid.